Hypoplastic Interface Model considering Plane Strain Condition and Surface Roughness - Yong-Gwang Jong; Yang Liu; Zixuan Chen; Pieride Mabe Fogang (Advances in Civil Engineering)
The soil-structure interface problem is an important part of soil-structure interaction research. These problems are mostly three-dimensional space problems, which is more complex to solve. In this paper, reduced stress and strain rate vectors are incorporated into the explicitly granular hypoplastic model by considering the plane strain state precisely. In addition, considering the important influence of roughness on the mechanical properties of contact surface, an improved hypoplastic model is established by incorporating the influence of roughness into the hypoplastic model, and the applicability of the new improved model is validated by comparing with the simulation results of the Mohr–Coulomb model, the explicitly granular hypoplastic models, and the experimental data. The results indicate that the improved model can be utilized to reflect the nonlinearity of the mechanical properties of the contact surface, which is in good agreement with the experimental data.